Metode Ijtihad Menurut Ibnu Hazm; Telaah Kitab al-Ihkām Fi Uṣūl al-Ahkām - A. Halil Thahir (LP2M Institut Agama Islam Negeri (IAIN) Kediri, 2016)
This article discusses Ushul al-Fiqh methodology of a famous intellectual from school of Zahiri, namely Ibnu Hazm through his work al-IhkÄm fi Uá¹£Å«l al-AhkÄm. Eventhough this school of thought cannot exist and be solid followed by muslims as like Sunni and Shiâ€™i schools of thought, the basis of methodology in formulating Islamic law can be investigated clearly especially in a book of al-IhkÄm fi Uá¹£Å«l al-AhkÄm written by Ibnu Hazm. By using text approach, this article analyzes Ibnu Hazmâ€™s thought which is stressing on a method of deciding Islamic law based on nash Al-Qurâ€™an and Al-Hadits. Therefore, the thought rejects every method based on reasoning as like al-Qiyas, al-Istihsan, al-Maslahah al-Mursalah etc. Moreover, it also rejects istidlal with dalil al-khitab approach which is still included in reasoning into texts of al-Qur`an dan al-Sunnah. The findings show that first, ijtihad formulation based on Ibnu Hazm is as follows: (a) it must be conducted based on three pillars of Islamic law sources namely Al-Qurâ€™an, Sunnah dan Ijmaâ€™ ; (b) if it cannot find zahir nash in the three pillars, Ibnu Hazm conducts ijtihad methods namely al-dalÄ«l which is devided into two namely dalil taking from nash Al-Qurâ€™an and Sunnah, dalil taking from ijmaâ€™. Second, the implication of Ibnu Hazmâ€™s ijtihad methodology into the construction of Islamic law is that the building of Islamic law is Al-Qurâ€™an and Sunnah, not others.